2020
DOI: 10.3390/insects11110735
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia’s Deleterious Impact on Aedes aegypti Egg Development: The Potential Role of Nutritional Parasitism

Abstract: The artificial introduction of the endosymbiotic bacterium, Wolbachia pipientis, into Aedes (Ae.) aegypti mosquitoes reduces the ability of mosquitoes to transmit human pathogenic viruses and is now being developed as a biocontrol tool. Successful introgression of Wolbachia-carrying Ae. aegypti into native mosquito populations at field sites in Australia, Indonesia and Malaysia has been associated with reduced disease prevalence in the treated community. In separate field programs, Wolbachia is also being used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 105 publications
(171 reference statements)
0
31
0
Order By: Relevance
“…Dissection of w AlbB-infected females that failed to lay eggs showed that all females were inseminated but lacked mature eggs in their abdomens despite being blood fed. Previous studies suggest that w AlbB has only a minor negative impact on egg viability during the first two months of storage [43]. However, these costs may be underestimated because a high proportion of females hatching from stored eggs are infertile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissection of w AlbB-infected females that failed to lay eggs showed that all females were inseminated but lacked mature eggs in their abdomens despite being blood fed. Previous studies suggest that w AlbB has only a minor negative impact on egg viability during the first two months of storage [43]. However, these costs may be underestimated because a high proportion of females hatching from stored eggs are infertile.…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia infections compete with their hosts for key nutrients required for egg production [44] which may be exacerbated when female parents are stored as eggs. Egg provisioning or hormone modulation may also be impacted by Wolbachia under stress [43, 45], but this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most drastic are their effects on female fertility, with almost all Wolbachia transinfections reducing fecundity or egg hatch (Axford et al, 2016, Fraser et al, 2017, Ant et al, 2018. These negative effects become pronounced with age, such as when eggs are quiescent (Allman et al, 2020), or appear under poor nutritional conditions (Caragata et al, 2014). Consequently, the negative effects of Wolbachia strains are likely to be underestimated when evaluated under standard laboratory conditions.…”
Section: Host Fitness Costsmentioning
confidence: 99%
“…When costs are triggered by environmental conditions, such as high temperatures or low rainfall, releases of Wolbachia-infected mosquitoes can be timed to facilitate the spread of Wolbachia when costs are low, followed by seasonal suppression when costs are high (Rašić et al, 2014. Most Wolbachia transinfections in mosquitoes reduce the viability of quiescent eggs (Allman et al, 2020), making it possible use these strains for population suppression during long dry seasons when rainfall is infrequent. Aedes aegypti carrying the wMel strain of Wolbachia become partially selfincompatible at high temperatures (Ross et al, 2019b), which may decrease population sizes during the hottest times of the year.…”
Section: Population Suppressionmentioning
confidence: 99%
See 1 more Smart Citation